P84 Clinical features and outcome of hepatopulmonary syndrome in children with chronic liver disease – single-centre experience at a paediatric liver unit in Singapore. (28th September 2020) - Wong, Sarah; Chiou, Fang Kuan; Phua, Kong Boo
Abstract : Objective: Hepatopulmonary syndrome (HPS) is a life-threatening complication of chronic liver disease. This study aims to examine the clinical profiles and treatment outcomes of HPS in paediatric patients at a tertiary hospital in Singapore. Method: A retrospective study of patients aged 0– 18 years diagnosed with HPS from 1987 to 2019 was conducted. HPS was diagnosed based on evidence of arterial deoxygenation, intrapulmonary vascular dilatations/shunting, on background of chronic liver disease and/or portal hypertension. Results: Five patients were included with median age of 11 years (range 3– 17) and median follow-up duration of 2 years (range 4 month-20 years). Underlying aetiologies included biliary atresia (n=3), autoimmune hepatitis (n=1) and glycogen storage disease type 3 (n=1). Digital clubbing was consistent in all cases, but only 1 patient experienced dyspnoea. Median oxygen saturation on pulse oximetry was 94.5% (range 91– 97). All 5 patients demonstrated intrapulmonary shunt (IPS) on contrast echocardiography (n=3) and/or lung perfusion study (n=3). Other complications of portal hypertension included variceal haemorrhage (n=3) and ascites (n=2). Median bilirubin, albumin and prothrombin values were 59 umol/L (range 33– 629), 32 g/L (range 27–33) and 16.1 seconds (range 13.2– 48.2). Three patients showed improvement in oxygenation with optimisation of liver disease and nutrition while awaiting transplant. Three patients underwent successful liver transplantation at median interval of 23 months (range 1– 94) from HPS diagnosis. Conclusion: Clinical onset of HPS in children can be subtle and correlates poorly with liver biochemistry and severity of portal hypertension. Early assessment for IPS and use of pulse oximetry may detect earlier and milder stages of HPS which may be reversible.